Survival disparities and competing mortality risks in offspring of consanguineous marriages in Yemen: A 26-year retrospective cohort analysis - Naif Taleb Ali; Mansour Abdulnabia H. Mehdi; Radfan Saleh Abdullah (PLoS ONE, 2026)
Background Consanguineous marriage is prevalent in many global populations and increases the risk of autosomal recessive genetic disorders in offspring. However, long-term disorder-specific survival patterns and competing mortality risks in this population remain poorly quantified, limiting evidence-based prognostic counseling and healthcare planning. Objective This study aimed to determine disorder-specific survival disparities, quantify cause-specific mortality using competing risks analysis, and evaluate the independent effect of the degree of consanguinity on mortality. Methods We conducted a 26-year retrospective cohort study (1998–2024) of 3,427 offspring from 1,065 Yemeni families. Vital status and cause of death were ascertained through multi-source verification. Survival analysis employed Kaplan–Meier estimators, Cox proportional hazards models, and Fine–Gray competing risks regression. Results Five-year survival varied substantially: 42.3% for hemoglobinopathies, 65.1% for congenital anomalies, 78.2% for neurodevelopmental disorders, and 92.4% for sensory impairments. First-cousin offspring had a 2.8-fold higher adjusted all-cause mortality risk (HR = 2.84, 95% CI 2.32–3.44) than non-consanguineous offspring. Competing-risks analysis revealed distinct age-specific mortality patterns: congenital anomalies dominated infant mortality (cumulative incidence 24.3%), whereas hematological disorders peaked in early childhood (18.7%). Conclusion Survival in consanguineous offspring shows severe disorder-specific disparities and a strong mortality gradient with the degree of consanguinity. The competing-risks framework provides critical insights for prognostic counseling and for prioritizing early interventions targeting high-risk disorders during critical mortality periods.